Research Spotlight: Designing nature-based mitigation to promote multiple benefits. Issue 2 (April 2013) - Busch, Jonah; Ahumada, Jorge; de Koning, Free; Harvey, Celia A; Hewson, Jenny; Hole, David; Honzák, Miroslav; Panfil, Steven N; Pidgeon, Emily; Portela, Rosimeiry; Steininger, Marc; Tabor, Karyn; et al.
By promoting the conservation and restoration of natural ecosystems, policymakers have a unique opportunity to mitigate climate change while providing social and environmental benefits. Here we highlight how nature-based mitigation strategies for multiple benefits can be supported by three key areas of scientific research, drawing upon examples of research by Conservation International and its partners. First, monitoring of ecosystems can quantify the magnitude of emissions released from conversion and degradation, and can inform prioritization and planning efforts. Second, understanding the synergies and tradeoffs between climate change mitigation and other ecosystem benefits can aid in designing policy instruments, selecting management techniques and geographically targeting actions. And third, research on the design of policies, incentives and practices can enhance mitigation initiatives' provision of both climate and noncarbon benefits. Achieving multiple benefits can in turn increase the sustainability of and investment in nature-based mitigation.